The Jewish Harmonious Social Relations with Islamic Societies: A Review of the Qur'an & History - Megawati, Lydia; Sohrah, Sohrah (Jurnal Adabiyah, 2023)
Religious tolerance is very necessary in social interactions. This has been seen in the interaction between Jewish and Muslims since ancient times. This research seeks to conduct a thorough evaluation of the positive social interactions between the Jewish and Islamic people. The researchers used both historical and Qur'anic methodologies in this investigation. This research examines the history that has been written about the interactions between Jewish and Muslim societies in light of both history and the Qur'an. By detailing the data sources and providing interpretations based on the Qur'an, the researchers carried out data analysis. The research findings indicate that Jews and Islamic civilization are rather close. The Qur'anic passages on Jewish people's ethics and history are numerous. The Qur'an has a number of verses that generally criticize Jewish or children of Israel and the people of the Book, but it also contains verses that counteract this and even exalts them. According to historical evidence, Jewish and Muslims lived side by side in harmony and peace from the time of the prophets through the years that followed, all the way up to the modern era. الملخص التسامح الديني ضروري جدا في التفاعلات الاجتماعية. وقد ظهر هذا في التعامل بين اليهود والمسلمين منذ العصور القديمة. يناقش هذا البحث التفاعلات الاجتماعية الإيجابية بين المجتمعين اليهودي والإسلامي. واستخدم الباحثون المنهج التاريخي والقرآن الكريم في جمع البيانات. يتناول هذا البحث التاريخ المكتوب عن التفاعلات بين المجتمعين اليهودي والإسلامي، سواء من حيث التاريخ أو القرآن. تم إجراء تحليل البيانات من خلال تفصيل مصادر البيانات وتقديم تفسيرات بناءً على القرآن. تظهر نتائج البحث أن الحضارتين اليهودية والإسلامية قريبتان جدًا. والآيات القرآنية المتعلقة بأخلاق وتاريخ الشعب اليهودي كثيرة. يحتوي القرآن على عدد من الآيات التي تنتقد بشكل عام اليهود أو بني إسرائيل وأهل الكتاب، ولكنه يحتوي أيضًا على آيات تعارض ذلك بل وتمجدهم. واستنادا إلى الأدلة التاريخية، عاش اليهود والمسلمون جنبا إلى جنب في وئام وسلام منذ زمن الأنبياء وحتى السنوات التالية، حتى العصر الحديث مفتاح البحث: اليهودية; المجتمع الإسلامي; التوراة; القرآن; التاريخ; العلاقات الاجتماعية Abstrak Toleransi beragama sangat diperlukan dalam suatu interaksi sosial. Hal tersebut terlihat pada interaksi Yahudi dan Islam sejak dari dulu. Penelitian ini membahas interaksi sosial positif antara masyarakat Yahudi dan Islam. Peneliti menggunakan metodologi sejarah dan Al-Qur'an dalam pengambilan data. Penelitian ini mengkaji sejarah yang pernah ditulis tentang interaksi antara masyarakat Yahudi dan Islam baik ditinjau dari sejarah maupun Al-Qur'an. Analisis data dilakukan dengan merinci sumber data dan memberikan tafsir berdasarkan Al-Qur’an. Hasil penelitian menunjukkan bahwa peradaban Yahudi dan Islam cukup dekat. Ayat-ayat Al-Qur'an mengenai etika dan sejarah orang Yahudi sangat banyak. Al-Qur'an mempunyai sejumlah ayat yang umumnya mengecam orang-orang Yahudi atau Bani Israil dan Ahli Kitab, namun juga memuat ayat-ayat yang menentang hal tersebut dan bahkan mengagung-agungkan mereka. Berdasarkan bukti sejarah, kaum Yahudi dan Muslim hidup berdampingan secara rukun dan damai sejak zaman para nabi hingga tahun-tahun berikutnya, hingga zaman modern. Kata Kunci: Agama Yahudi; Masyarakat Islam; Taurat; Al-Qur'an; Sejarah; Hubungan Sosial